2021
DOI: 10.3389/fneur.2021.650884
|View full text |Cite
|
Sign up to set email alerts
|

High-Molecular-Weight Hyaluronic Acid Vehicle Can Deliver Gadolinium Into the Cochlea at a Higher Concentration for a Longer Duration: A 9.4-T Magnetic Resonance Imaging Study

Abstract: Intratympanic (IT) gadolinium (Gd) injection is one method of delivering Gd into the inner ear to evaluate the amount of endolymphatic hydrops (EH) using magnetic resonance imaging (MRI). As Gd is usually prepared in a fluid form mixed with saline, Gd injected into the middle ear drains easily through the Eustachian tube within several hours. High-molecular-weight (hMW) hyaluronic acid (HA) is an ideal vehicle for IT Gd due to its viscous and adhesive properties. The present study was performed to elucidate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The minute gaps between the ossicles and the round window niche might serve as crucial anatomical sites where HHA remains for extended durations, subsequently acting as a reservoir for D. Consequently, the concentration of D phosphate in the cochlear perilymph was about double that of the saline + D group. In previous research, the concentration of gadolinium was also observed to be 1.9–2.1 times higher in the HHA group compared to the saline group ( Hwang et al, 2021 ). We speculate that the elevated drug concentration in the cochlea is attributable to the extended residence of the HHA vehicle within the middle ear.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The minute gaps between the ossicles and the round window niche might serve as crucial anatomical sites where HHA remains for extended durations, subsequently acting as a reservoir for D. Consequently, the concentration of D phosphate in the cochlear perilymph was about double that of the saline + D group. In previous research, the concentration of gadolinium was also observed to be 1.9–2.1 times higher in the HHA group compared to the saline group ( Hwang et al, 2021 ). We speculate that the elevated drug concentration in the cochlea is attributable to the extended residence of the HHA vehicle within the middle ear.…”
Section: Discussionmentioning
confidence: 72%
“…Compared to conventional HA (molecular weight ≤3 MDa), HHA is more robust and adhesive ( Figure 1 ). Prior research has highlighted the differences in physical properties and 9.6T MR imaging-based pharmacokinetics between HHA and conventional HA ( Hwang et al, 2021 ). HHA demonstrated the ability to deliver higher gadolinium concentrations to the cochlea over an extended period without adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Our micro-CT data showed that the dual vehicle stayed in the middle ear for several weeks. This residual volume of drug/vehicle can provide a continuous drug supply to the inner ear (Hwang et al, 2021). When conventional HA was used as a vehicle, the vehicle stayed in the middle ear for only 2 days and the treatment effect was limited (Park et al, 2020).…”
Section: Discussionmentioning
confidence: 99%